THE STRENGTH BEHIND GROWTH: EXPLORING METAPHORS IN PAUL LAURENCE DUNBAR’S POEM, THE SEEDLING - Fitriyah, Fitriyah; Suroso, Aisyah Ahzahra; Maharani, Arvina Septa (Language Literacy: Journal of Linguistics, Literature, and Language Teaching, 2024)
This research analyzes the types of metaphors in Paul Laurence Dunbar’s ‘The Seedling’ using Lakoff and Johnson’s conceptual metaphor theory. A metaphor is a figure of speech that compares two different things. A metaphorical poem has the ability to create and translate the figurative language contained in the content of the poem, especially where there are deep personal and emotional experiences”." The research uses descriptive qualitative methods to obtain a clear and systematic description of the metaphors found in this poem. The findings show that there are three kinds of metaphors identified in the poem "The Seedling." Those are ontological, image scheme, and orientational. The metaphors used in Paul Laurence Dunbar's 'The Seedling' speak to the stages of human improvement, utilizing characteristic pictures such as seeds, roots, daylight, and rain. Each allegory is utilized to portray desires, dreams, trusts, and the plausibility of developing into a grown up in spite of having to overcome numerous challenges. Understanding the meaning and function of metaphors will broaden our conception of language as a learning medium with strong implications for language and literacy teaching.